ANALISIS KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL MATERI ARITMATIKA SOSIAL MELALUI PEMBELAJARAN DARING - Nita Nopita; Tina Rosyana (IKIP Siliwangi, 2021)
The current situation is hit by the COVID-19 pandemic, so research is carried out through online learning on social arithmetic material with the aim of describing and knowing students' difficulties when working on questions. The data collection technique used Google forms and the research subjects were in class VIII H at SMPN 1 Nagreg, totaling 20 students. The method in this research is descriptive qualitative, the research instrument is a test of social arithmetic material in the form of 5 description questions. Factors that cause difficulties in working on social arithmetic problems, including: (1) in understanding the questions students have difficulty (2) students find it difficult to transform questions; and (3) students find it difficult to work on the questions. The results of this study obtained data that it is still difficult for students to solve social arithmetic problems. The percentage value of students' answers is mostly on the indicators determining gross, net and tare in the cognitive domain of C5 with a percentage of answers of 35% including the very low category.